DIAGNOSTICS OF BROILER SALMONELLOSIS ON A PRIVATE FARM - Peredera, O. O.; Peredera, R. V.; Savchenko, K. S. (Scientific Progress & Innovations, 2020)
The article presents the main points of diagnostics, elimination and prevention of broiler salmonellosis. During the studies, epizootic process of the disease in dynamics was investigated. The synchronicity of catching the disease by a significant number of birds, changing feed for the group of poultry, in which the disease was registered, was taken into account. One of the components of combined feed (meat and bone meal) was of doubtful origin, privately produced. Clinical signs were not characteristic for salmonellosis. The chickens rapidly developed depression. Broilers refused to eat. Anemia was quite noticeable while studying the skin of the crest, gills and mucous membranes. Hens sat ruffling up feathers, and died 1-2 days after appearing the first clinical signs. The pathological changes detected at autopsy were typical for avian salmonellosis. Changes resulting from sepsis were well noticed. The most characteristic pathological changes were found in the spleen, heart, liver and small intestine. Changes in the liver of most broiler chickens indicated long-term toxic processes, which could be associated not only with the intensive propagation and discharge of endotoxins by pathogenic microorganisms, but also by the action of fungal toxins. Signs of fibrinous peritonitis and numerous synechias in the abdomen were registered in all broilers at autopsy. Kidney enlarging was also registered. After isolating pure salmonella culture from the internal organs of dead poultry and from compound feed, a batch of test feeds containing the infected meat and bone meal was recommended to be removed from the diet. Pieces of internal organs of dead poultry, samples of feed, meat and bone meal were the materials for bacteriological and mycological examination. During bacteriological studies specific nutrient media were used: Endo medium, Ploskirev agar, Levin medium, and bismuth sulfite agar. Samples of feed, meat and bone meal to detect pathogenic fungi were incubated on Saburo agar. As a result of bacteriological analysis, salmonella causative agent was found in the internal organs of dead poultry, combined feed, meat and bone meal. The growing of salmonellosis pathogen on differential nutrient media was characteristic, rapid and intensive. Fungi of Aspergilus genus were found in samples of combined feed, meat and bone meal. Determining the sensitivity of isolated micro-flora to medicines is one of the important points in treatment of infectious diseases. To determine the sensitivity of microorganisms to antimicrobials by disco-diffusion method in accordance with generally accepted NCCLS standards, Mueller- Hinton agar was used. According to the results of studies, the isolated salmonella culture was resistant to polymyxin, tylosin, neomycin, tetracycline, laevomycetin, rifampicin, decamethoxine. The pathogen showed moderate resistance to gentamicin, kanamycin, cephalosolin. On the studied private farm, pure culture of the isolated pathogen showed the highest sensitivity to amoxicillin.